Death anxiety, altruism, self‐efficacy, and organ donation intention among Japanese college students: A moderated mediation analysis. (14th December 2012) - Wu, Anise M. S.; Tang, Catherine S.; Yogo, Masao
Abstract: The shortage of organs for transplantation in Japan has alerted health professionals to the low organ donation rate among Japanese people. The unique cultural view of death and altruism has been suggested leading to their low intent to donate cadaveric organs. A cross‐sectional survey was conducted in Japan to investigate the interplay of death anxiety, altruism, and self‐efficacy in influencing Japanese college students' intention to sign donor cards, in order to mobilise this large potential source of organ donors in the future. Six hundred and seven Japanese non‐donor card signers voluntarily completed a self‐administered questionnaire. The results of mediation and moderated mediation analyses with bootstrap approach suggest that death anxiety indirectly hinders Japanese people's intention to become a donor card signer through lowering of self‐efficacy, while altruism intensifies the positive impact of self‐efficacy on signing intention. These findings provide useful insights for organ procurement organisations seeking behavioural change not only in Japan but also in multi‐ethnic societies with a substantial Japanese population.